KARAKTERISASI DAN SKRINING FITOKIMIA DAUN KEREHAU (Callicarpa longifolia Lamk.) - Supomo -; Risa Supriningrum; Risaldi Junaid (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2016)
Plants kerehau empirically used to treat swelling, abdominal pain and diarrhea. Kerehau leaf research data related to quality botanicals have not done, this causes the botanicals and extracts do not have a standard. The purpose of this study to determine the chemical characterization and the compound leaf extract botanicals and kerehau. The research object leaves kerehau obtained from the village of Muara District Muara Aloh Muntai, made crude drug samples are extracted using maceration method by ethanol 70%. Then examined the macroscopic, microscopic, these characterizations include: water assay, assay of soluble extract in water, soluble extract assay of ethanol, the determination of ash content and assay of acid insoluble ash is then performed phytochemical screening. Data were analyzed using descriptivemethods. The characterization results simplicia, macroscopic kerehau has green leaves, pointed leaf tip, leaf base tapering, serrated leaf edge, the shape of elongated leaves, a single leaf, leaf arrangement pinnate, pinnate leaves arrangement of bones, flesh soft thin leaves, leaf length 10,5- 14 cm and 4-6 cm wide leaves. Microscopic hair bulbs discovered fragment identifier cover, file vessels, glands hair, and stomata calcium oxalate crystal anisositik. The water content of 9.6%, water soluble extract content of 17.7% ethanol soluble extract content of 11.3%, ash content of 6%, acid insoluble ash content of 1%. The characterization results extract ethanol, 15% water content, water soluble extract content of 40.4% ethanol soluble extract content of 39.9%, ash content of 3.5%, acid insoluble ash content of 0.3%. While the results of the identification of classes of chemical compounds, known kerehau leaf contains flavonoids, tannins, saponins and terpenoids.